Men of Steel : 6 Armoured Division in the 1965 War - Abrar Husain, Maj. Gen. (GHQ, Rawalpindi Army Education Publishing House, 2005)
This book is an account of the 1965 war between Pakistan and India, based on the war despatches of Major General Abrar Husain, General Officer Commanding 6 Armoured Division.
Include Illustrations, Annexures, Glossary and Index.
An account of the war between Pakistan and India in 1965.
Keywords: Pakistan -- Regimental histories -- India-Pakistan Conflict (1965)